Income distribution - Campano, Fred.; Salvatore, Dominick (New York : Oxford University Press, 2006)
Suitable for undergraduate economics majors, this text also serves the needs of sociologists and political scientists who are interested in the related social injustice topics of income equality and poverty. Each chapter is logically connected with the preceding chapters, providing a general overview of income distribution and its applications.
Includes bibliographical references (p. 165-170) and indexes.
oif 30/04/15
Loan
Keywords: Income distribution; Income distribution -- Government policy